ANALISIS HYGIENE DAN SANITASI MAKANAN GUNA MENUNJANG MUTU PELAYANAN UNIT GIZI DI RUMAH SAKIT MUHAMMADIYAH BANDUNG - Nurul Dwi Ariyani; Etik Kartika (INFOKES (Informasi Kesehatan), 2021)
This study aimed to determine the hygiene and sanitation of food to support quality service of Nutrition Unit at Muhammadiyah Hospital Bandung. The research methods used, that were qualitative method with descriptive approach. The data collection techniques used were observation, interview and literate study. From the results of researches conducted of Nutrition Unit at Muhammadiyah Hospital Bandung, there were several problems found, namely: (1). The bin is not separated between dry and wet junk. (2). Cooking utensils leave crusty stains like woks and pans. (3). Officers do not used full personal protectived equipments (4). The officers did not use masks and gloves. The writer suggested, namely: (1). Provided a trashs bin between dry and wet bin. (2). Changing equipments review proces equipment already looks not feasible used. (3) Complied the procedures or regulations applicable to all assigned tasks.